The Effectiveness of ASEAN Cooperation in Marine Environmental Protection (MEP) in South China Sea (SCS) - Yoga Suharman; Suratih Muhamad Karo (Universitas Muhammadiyah Yogyakarta, 2020)
This research aims to examine ASEAN cooperation in responding to issues related to marine environmental security due to the exploration of resources in the South China Sea (SCS) region. This research analyze two aspects of environmental security, consist of (1) ASEAN’s collective role in maintaining environmental security and production in the SCS to realize environmental and human security, and (2) the effectiveness of ASEAN cooperation in responding to environmental problems in the SCS through international regime effectiveness theory developed by Arild Underdal. This study utilized a qualitative method by comparing the development of ASEAN MEP cooperation and problem-solving capacity before and after the Declaration for a Decade of Coastal and Marine Environmental Protection in the South China Sea containing institutional setting, power distribution, instrumental leadership, and collaboration level between ASEAN, the epistemic community, and behavioral changes. Data and information obtained from primary sources such as ASEAN official documents and secondary sources consisted of scientific journals and web articles. The findings indicate that ASEAN MEP cooperation has developed towards effectiveness but has not reached the optimum point in solving maritime problems in the SCS.